(untitled) (El Taco en la Brea, 2017)
«Some Statements and Truisms about Neologisms, Newisms, Postisms, Parasitisms, and Other Small Seisms»,de Jacques Derrida. En Derrida d’ici, Derrida de là. Thomas Dutoit y Philippe Romanski, editores. París: Galilée, 2009.